Delimitation of the warm and cold period of the year based on the variation of the Aegean sea surface temperature - MAVRAKIS, A.; LYKOUDIS, S.; THEOHARATOS, G. (Mediterranean Marine Science, 2004)
Knowledge of the warm and cold season onset is important for the living conditions and the occupational activities of the inhabitants of a given area, and especially for agriculture and tourism. This paper presents a way to estimate the onset/end of the cold and warm period of the year, based on the sinusoidal annual variation of the Sea Surface Temperature. The method was applied on data from 8 stations of the Hellenic Navy Hydrographic Service, covering the period from 1965-1995. The results showed that the warm period starts sometime between April 28th and May 21st while it ends between October 27th and November 19th in accordance with the findings of other studies. Characteristic of the nature of the parameter used is the very low variance per station – 15 days at maximum. The average date of warm period onset is statistically the same for the largest part of the Aegean, with only one differentiation, that between Kavala and the southern stations ( Thira and Heraklion).